The attractiveness of the Singapore sailing federation to sponsors - Khng, Griselda (2014)
Campaigning for the Olympic Games can be very expensive and external financial aid can greatly help Olympic sailors sustain their campaign. Therefore, it is important for their sailing federations to help them attain sponsorship deals, in order to lessen their financial burden and enable them to afford equipment, gears, and other expenses. Interviews were conducted to identify the similarities and differences between the various international sailing federations with prestigious sponsors, to ascertain what the Singapore Sailing Federation is lacking. Results suggested that bagging previous Olympic Games medals and having strong sporting cultures are critical in attaining sponsorship deals with prestigious companies.